Electrochemical immunosensor for individual and simultaneous determination of Cytokeratin fragment antigen 21-1 and Neuron-specific enolase using carbon dots-decorated multiwalled carbon nanotube electrode - Filik, Hayati; Avan, Asiye Aslihan; Puntar, Nilay Altas; Ozyuerek, Mustafa; Cakici, Maside; Guengor, Zeynep Banu; Kucur, Mine; Kamis, Handan (ELSEVIER, 2022)
In this approach, we fabricated a sandwich-type electrochemical immunosensor for individual and simultaneous sensing of cytokeratin fragment antigen 21-1 (CYFRA 21-1) and neuron-specific enolase (NSE) using the multiple-label concept. In this report, carbon dots (CDs) were prepared from citric acid and ethylenediamine (EDA). A hybrid EDA-CDs-MWCNTs composites were prepared and then decorated with gold nanoparticles (AuNPs). The obtained hybrid composites were used as an immunosensing platform. Furthermore, AuNPs decorated EDA-CDs-MWCNTs was carefully loaded with reactive dye (orange G and carminic acid) and utilized as signal labels. The surface morphology and the electrochemical properties of the modified SPCE were studied carefully. The linear range for the individual and simultaneous detection was 0.002-10 ng mL-1 for the CYFRA 21-1 and NSE and the detection limits (LODs) were 0.22 pg mL-1 and 0.15 pg mL-1 for the individual detection while 0.25 pg mL-1 and 0.20 pg mL-1 for simultaneous detection, respectively. This developed immunoassay was utilized for the assessment of two markers in the serum sample with reasonable consequences.
Keywords: Cytokeratin fragment antigen 21-1; Neuron-specific enolase; Immunosensor; Voltammetry; Serum analysis; MULTIPLE TUMOR-MARKERS; CELL LUNG-CANCER; 4 BIOMARKERS; 3D GRAPHENE; IMMUNOASSAY; BIOSENSORS; NANOCOMPOSITES; NANOPARTICLES; OXIDATION; PLATFORM; Chemistry